Sistem Pendukung Keputusan Berbasis Android untuk memberi Rekomendasi Jodoh dengan menggunakan Metode Simple Additive Weighting - Joseph Pranata Onggo Sanusi; Lily Puspa Dewi; Justinus Andjarwirawan (Jurnal Infra, 2017)
During this match is done by way of introduction process intended to get married. In general, introductions are conducted by exchanging biodata between men and women accompanied by intermediaries such as parents, close relatives, friends or dating agency. This is of course difficult for men and women who want to find a mate because if men and women want to meet, they must meet face to face. In addition without the use of communication tools men and women will not be able to express their feelings.This application is created using the programming language PHP, Java and MySQL database. App view using Android Studio 2.2 program. Chat feature using chat messenger telegram template.The end result of this application development is able to show recommendation of candidate pair according to result of calculation, fill criteria value according to desire, answer criteria question, add friendship, chat between users, give notification to user, and change answer and criteria value. Users can also see some personal information about candidates for recommendations that are displayed such as name, age, city and date of birth.